A4.22 Syndecan-4 controls interleukin (IL)-1 receptor trafficking and IL-1 signalling in chronic destructive arthritis. (13th February 2015) - Godmann, L; König, U; Stratis, A; Cromme, C; Neugebauer, K; Herzog, C; Korb-Pap, A; Niederreiter, B; Dankbar, B; Redlich, K; Echtermeyer, F; Pap, T; et al.
Abstract : Background and objectives: Syndecan-4 (sdc4) is a transmembrane heparan sulfate (HS) proteoglycan. We have shown previously that sdc4 blockade protects from osteoarthritis like changes in mice. Here, sdc4 has been implicated in the modulation of IL-1 mediated Erk signalling and regulation of MMP-3 expression in fibroblasts by modulating IL-1 receptor trafficking. Hence, we hypothesised that sdc4 blockade reduces cytokine signalling in RA synovial fibroblasts. Materials and methods: Evaluating the impact of sdc4 on the RA phenotype in vivo, hTNFα transgenic (hTNFtg), sdc4 knockout (sdc4 -/- ) and hTNFtg/sdc4 -/- as well as hTNFtg mice treated with sdc4 blocking antibody were histological analysed. To quantify the histomorphometrical changes toluidin-blue stained sections were analysed for cartilage destaining and erosion. Furthermore, immunohistological stainings for MMP-3 and the IL-1 receptor (IL-1RI) were performed. MMP-3 production was analysed via ELISA after TNFα or IL-1 stimulation and the influence on the Erk signalling pathway was evaluated by Western blot analysis in cells lacking sdc4, IL-1RI or both proteins. Additionally, the expression and presentation of TNF and IL-1RI was assessed via quantitative RT-PCR and FACS analysis. Influence of IL-1 stimulation on sdc4 complex formation was characterised via crosslinking and subsequent Western blot detection. Results: The loss of sdc4 or its antibody-mediated inhibition reduced the severity of chronic destructive arthritis in mice by impairing IL-1 responsiveness of resident fibroblast-like cells. RT-PCR revealed, that neither the expression of IL-1RI nor TNF receptor was altered in cells lacking sdc4 compared to wild type fibroblasts, whereas FACS analysis and histological stainings showed that the inhibition of sdc4 largely abolished the IL-1R presentation on fibroblasts in vitro and in vivo . We demonstrated that IL-1 directly binds to sdc4 and in an IL-1R independent manner leads to its dimerisation. Strikingly, IL-1 induced dimerisation of sdc4 and its loss diminished caveolin vesicle-mediated trafficking of IL-1RI. Hence, Western Blot analysis of Erk phosphorylation showed reduced IL-1 induced Erk1/2 phosphorylation in sdc4 -/- compared to wild type fibroblasts. The absence of IL1RI prevented IL-1 mediated Erk1/2 phosphorylation completely. Focusing at MMP-3 levels as read-out for the activation of the Erk-pathway, we found lower MMP-3 production upon IL-1 stimulation in sdc4 -/- compared to wild type controls, while IL-1RI -/- cells did not respond at all. MMP-3 production was not altered upon TNFα stimulation. Conclusion: We could show that the loss plus the antibody-mediated sdc4 blockade reduced IL-1RI presentation and thereby IL-1 signalling in firboblasts, which constitutes a novel function of sdc4 and might be of great value for RA treatment.